THE HISTORY OF THE DEVELOPMENT OF CRIMINAL COURTS IN UZBEKISTAN - Gulnoza Yusupdzhanova Ilxomovna (International Journal of Business, Law and Political Science, 2024)
The judicial system in Uzbekistan has undergone significant transformations from ancient times to the Soviet era, reflecting shifts in cultural, political, and legal frameworks. Early judicial practices in Central Asia were deeply rooted in indigenous traditions and religious doctrines, notably reflected in texts such as the "Avesta." The subsequent imposition of Russian colonial rule introduced a dual legal system combining secular and Sharia-based courts, further restructured during the Soviet period to align with Bolshevik ideologies. Despite extensive documentation of these historical developments, there is a lack of comprehensive analyses that integrate the evolution of criminal courts within the broader socio-political context of the region. This study aims to provide a detailed historical overview of the criminal judicial system in Uzbekistan, examining how local traditions, colonial influences, and Soviet reforms shaped its development. The research reveals that the ancient judicial practices were characterized by culturally ingrained methods of dispute resolution, which were significantly altered by Russian legal reforms and further transformed by Soviet judicial policies. By tracing the continuity and change in judicial practices from pre-colonial to Soviet times, this study highlights the dynamic interplay between indigenous legal traditions and external legal frameworks, offering new insights into the adaptation and evolution of criminal justice in Uzbekistan. Understanding these historical changes provides valuable context for contemporary legal reforms and highlights the enduring impact of historical practices on the modern judiciary. This analysis contributes to the broader field of legal history and offers a nuanced perspective on the development of judicial institutions in post-colonial societies.